Reliability and validity indices of the Philippine Science High School entrance test - De Leon, Rosalinda S. 1939- (s.n.], 1969)
The purpose of this research is to determine the viability and reliability of the the Science and Mathematics Aptitude Test as a screening instrument for the selective admission function of the Philippine Science High School.